THE ROLE OF AWARENESS IN SECOND LANGUAGE DEVELOPMENT - Fahriany, Fahriany (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2014)
Cognitive psychology and cognitive science appear to agree that attention to stimuli is needed for long-term memory storage and that little, if any, learning can take place without attention. One strand of psycholinguistic research that has drawn quite a lot of interest, both from a theoretical and empirical perspective, is the role awareness plays in second language acquisition (SLA). To promote a further understanding of the role of awareness may potentially contribute to L2 development. This article willÂ briefly describe current theoretical approaches to the role of awareness in language learning,Â review recent studies that have employed verbal reports to investigate the effects of awareness on L2 development, andÂ provide, based on the review, some awareness-raising pedagogical tasks for the L2 classroom setting.Keywords: attention, awareness, detection, feedback, L2 development